Marine Expeditions in Indonesia during the Colonial Years - Herman Darman (Berita Sedimentologi, 2015)
During the colonial years there was little support from the Netherlands government for non-applied scientific work. The colonies had to pay for themselves and had to be profitable for the Netherlands; science was not considered to be a good investment. Nevertheless, a number of important oceanographic expeditions took place, for example, the Siboga and Snellius expeditions. Both were named after the ships that carried the scientists and both were paid for by the Netherlands government. The objective was to prove that the Dutch Indies were not only the best governed, but also the scientifically most developed tropical colony. Moreover there were the Dutch who needed to consolidate colonial rule by showing the flag over the whole archipelago. Germans, British, Americans and Japanese were encroaching on the Far East (New Guinea, Philippines, Malaysia and Taiwan) and in some ways the expedition can be considered as ‘gunboat science’. Even so, vast amount of prime oceanographical, hydrographical, biological and geological data were collected with state-of-the-art equipment.